Do boxing athletes differ from controls in visually analysing opponent´s postures? A pilot study tracking eye movements - Tessari, A.; Lugli, L.; Nicoletti, R.; Ricciardelli, P. (Journal of Human Sport & Exercise, 2021)
Boxing athletes code the opponents` intention to act in advance to plan and perform the most appropriate counterattack responses; in contrast, non-athletes respond with a defence action (Ottoboni, Russo, Tessari, 2015). We investigated whether such difference is limited at elaborating the most appropriate motor response or relies on different visual and attentional strategies during the early visual analysis of the opponent. We recorded saccades as indexes of visual attentional orienting during an implicit paradigm (i.e., a Simon-like task): nine experienced boxers and nine controls observed photographs of boxing attacks (jab and cross) or a neutral position (guard) and judged the colour of body parts either salient or not for elaborating the attack action (gloves vs. shorts, respectively) by shifting their gaze towards one of two lateral response boxes. Release reaction times (i.e., time between the start of the first saccade away from the fixation rectangle toward the response box) were faster toward the arm that seemed about to attack for the jab stance (the most dynamic one as implying motion) when judging the glove colour in both athletes and controls. No effect emerged when focusing on the shorts that provide irrelevant information for elaborating a defence or attack action. Therefore, athletes and controls seem to use the same visual strategies (saccadic movements) when analysing the opponent`s posture before acting. However, if expertise brings better motor response processing as previously found, the difference between athletes and non-athletes must lay in a later cognitive stage (other than the visual one) devoted to plane the most effective motor response.